ANALISIS NILAI KARAKTER DALAM FILM ANIMASI UPIN DAN IPIN GENG PENGEMBARAAN BERMULA KARYA NIZAM RAZAK - Muhammad Yudistira Firdaus; Erik Candra Pertal; Siska Hestiana (Yayasan Nusantara Hasana Berdikari, 2023)
Instilling character in children must be done from an early age, because forming character values requires a systematic and prolonged preparation of stages. The purpose of this study was to analyze the character values in the animated film Upin Dan Ipin Geng Pengembaraan Bermula by Nizam Razak. This type of research is qualitative research with descriptive methods. The data in this study was carried out using the animated film Upin Dan Ipin Geng Pengembaraan Bermula by Nizam Razak which contains character values. Data collection techniques used in this study through listening and taking notes in concluding the data. The data in this study were obtained by watching the animated film Upin Dan Ipin Geng Pengembaraan Bermula by Nizam Razak. Based on the results of analysis of research data through description, character values were found in the animated film Upin Dan Ipin Geng Pengembaraan Bermula Pemula by Nizam Razak. Character values are shown through the sentences and actions in each scene in the film. The results of this study indicate that there is a character value contained in the animated film Upin and Ipin Geng Pengembaraan Bermula by Nizam Razak.